A comparison of two simultaneous faults calculation methods based on sequence-domain and phase-domain frame of representation - Ranola, Jo Ann P. (2004)
The project aims to develop a computer program that would implement two simultaneous faults calculation by using two methods based on sequence-domain and phase-domain frame of representation. For the method based on sequence-domain, Z. X. Han's solution method was used. In his proposed methodology, the two-network theory is applied to get an equivalent positive sequence network. The augmented positive-sequence network (APSN) that is formed is in terms of admittance or impedance matrix. For the method based on phase-domain, L. Roy and N.D. Rao's alternative approach was employed. In their technique, fault condition is considered as a modification of parameters of branches of the pre-fault network. The project also aims to reexamine the methodology and the underlying assumptions used in these important calculations. The two approaches was compared based on accuracy, solution time and data requirements. The program was compared based on accuracy, solution time and data requirements. The program is useful for electric power system analysis and design, relay protection and stability.
Thesis (B.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electric power systems; Electric power distribution; Fault calculations